PENGARUH ENKAPSULASI EKSTRAK DAUN MURBEI (Morus alba L.) TERHADAP TEKANAN DARAH ARTERI PADA TIKUS - Siti Aminah; Suwaldi Suwaldi; Achmad Fudholi; Wahyono Wahyono (Majalah Obat Tradisional, 2014)
Rutin and quercetin are   flavonoid compounds containing in the extract of mulberry (Morus alba L.) leaves  have an influence on the cardiovascular system. This study aims to assessment of the blood pressure effect and cardiac puls after giving ethanolic extract of  mulberry leaves.  The extract was made using 95% ethanol by remaseration method. The content of rutin and quercetin in the extract were determined by using HPLC(High Performance Liquid Chromatography).  The formula of the encapsulation containing extract 0.25% w/v, chitosan 0.5mg/mL and TPP (sodium  tripolyphosphate) 1mg/mL. Characterization of extract encapsulated was done on the particle size, encapsulation efficiency and FTIR. Extract encapsulated was given to rats orally,  subsequently arterial blood pressure and heart rate were measured using Coda Non-Invasive Blood Pressure System. The results showed that mulberry extract contains rutin (0.879±0.138) mg/g  and  quercetin (4.427±0.065) mg/g. Ratio of chitosan-TPP with 0.5:1  forms particle size were   25.11-45.2 nm, encapsulation efficiency  (76.14±2.29)%. Mulberry leaves extract and encapsulated extract could decrease arterial blood pressure.